2009
DOI: 10.1016/j.ijhydene.2009.06.080
|View full text |Cite
|
Sign up to set email alerts
|

Direct synthesis of MgH2 nanofibers at different hydrogen pressures

Abstract: ABSTRACT:This paper describes the direct synthesis of magnesium hydride (MgH 2 ) nanofibers by hydriding chemical vapor deposition (HCVD), in which the effect of hydrogen pressure on the production rate, the composition and the shape of products obtained were examined by using X-ray diffraction (XRD), scanning electron microscopy (SEM) and Brunauer-Emmett-Teller (BET). The XRD patterns showed that the main product in each case was MgH 2 ; in particular, the products formed at 2, 3 and 4 MPa were highly pure. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 33 publications
3
49
0
Order By: Relevance
“…It is an especially promising material owing to its quite high hydrogen capacity of 7.6 mass% and relatively low production cost. Saita et al, demonstrated that MgH 2 can be produced by hydriding chemical vapor deposition (HCVD) in which the MgH 2 absorbs and desorbs as much as 7.6 mass% hydrogen without any activation treatments [18][19][20], and clarified that the total exergy loss of metal hydride production process without activation treatment is smaller than conventional process [21].…”
Section: Introductionmentioning
confidence: 99%
“…It is an especially promising material owing to its quite high hydrogen capacity of 7.6 mass% and relatively low production cost. Saita et al, demonstrated that MgH 2 can be produced by hydriding chemical vapor deposition (HCVD) in which the MgH 2 absorbs and desorbs as much as 7.6 mass% hydrogen without any activation treatments [18][19][20], and clarified that the total exergy loss of metal hydride production process without activation treatment is smaller than conventional process [21].…”
Section: Introductionmentioning
confidence: 99%
“…the HCVD method, as described elsewhere. [8,9,11] 10 g of commercially available Mg powder (purity: 99%; particle size: < 75 µm) was placed in an Inconel tube and heated to vaporize in an H 2 atmosphere (purity: 99.99999%) at 4.0 MPa and at a temperature of 600 ºC for 20 hours. The reactants, namely, the H 2 and Mg in vapor form, were deposited on the cooled Inconel flange substrate of the reactor at a temperature of 400 ~ 500 ºC to form MgH 2 nanofibers.…”
Section: Methodsmentioning
confidence: 99%
“…Another solution is to reduce the size of the Mg/Mg-based materials to the nano-scale. In order to manufacture micro/nano-structured Mg or MgH 2 and their composites many processes, such as high-energy ball milling of MgH 2 or MgH 2 -based composites [3][4][5], magnetron sputtering for Mg thin films, [6] physical vapor-transport deposition (PVD) of Mg nanowires, [7] and hydriding chemical vapor deposition (HCVD) of MgH 2 nanofibers, [8][9][10] have been used. The as-prepared Mg nanowires by the PVD method having diameters ranging from 30 to 170 nm exhibit enhanced hydrogen adsorption kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Two commercially available, (a) large MgH 2 particles and (b) small MgH 2 particles with (average size, purity) = (60 m, 99 mass%) and (2 m, 90 mass%), were prepared by carrying out a gas-solid reaction (GSR) under specified conditions of temperature and pressure. Further, we produced (c) an MgH 2 nanofiber, having a diameter of 500 nm and length of several tens of microns by using hydriding chemical vapor deposition (HCVD) [24][25][26]. During HCVD, magnesium hydride was deposited on the inconel substrate via a gas phase reaction between magnesium vapor and high-pressure hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…During HCVD, magnesium hydride was deposited on the inconel substrate via a gas phase reaction between magnesium vapor and high-pressure hydrogen. The detailed procedure is described elsewhere [24][25][26]. Table 1 gives the physical characteristics of the abovementioned three samples; these characteristics were determined using X-ray diffraction with Cu-Kα radiation (XRD, Miniflex, Rigaku Co., Ltd.), a scanning electron microscope (SEM, Japan Electron Co., Pty.…”
Section: Introductionmentioning
confidence: 99%